Development and validation of a sliding type continuous passive motion automation device for evaluation and rehabilitation of frozen shoulder: a pilot study - Lee, Jewoo; Yun, Sung-sik; Oh, Kyung Rok; Chung, Sun Gun; Hwang, Wonjae; Kim, Keewon; Cho, Kyu-jin (Frontiers in Rehabilitation Sciences, 2025)
BackgroundFrozen shoulder (FS) is a condition that results in pain and restricted range of motion (ROM) in the shoulder joint, impacting daily activities. Current rehabilitation methods, including physical therapy and passive range of motion (PROM) exercise, can be limited by cost and availability. This study aimed to develop and test a novel robotic CPM device capable of measuring joint stiffness and improving accessibility and self-exercise effectiveness for FS patients.MethodsA 3-armed randomized clinical trial was conducted with 12 FS patients allocated into three groups: (1) hot pack treatment (negative control), (2) PROM by physiotherapists (active control), and (3) robotic CPM device-assisted exercise (intervention). ROM, pain levels using the Visual Analogue Scale (VAS), and the Shoulder Pain and Disability Index (SPADI) were measured at baseline, immediately post-intervention, and after a 6-week follow-up. A linear mixed model was applied for inter-group and intra-group analyses. Torque and stiffness were calculated using sensor data collected by the robotic device and Inertial Measurement Units (IMUs) for precise monitoring.ResultsThe intervention group showed significant improvement in ROM compared to the negative control group, particularly in external rotation (p = 0.022). Intra-group analysis for the intervention group revealed average ROM increases of 14.52∘, 16.72∘, and 14.19∘ for flexion, abduction, and external rotation, respectively. Passive stiffness in the intervention group significantly decreased in abduction (p = 0.010) and external rotation (p < 0.001). Pain levels and SPADI scores decreased across all groups, with no statistically significant differences noted between the intervention and the postive control groups.ConclusionsThe developed robotic CPM device demonstrated potential in improving ROM and reducing passive stiffness in FS patients, showing comparable results to therapist-assisted exercise. While the device enhances accessibility and self-monitoring capabilities, further studies are required to validate its use in home settings and assess its impact on long-term motivation for self-exercise.Clinical Trial RegistrationThe clinical trial was approved and registered under Seoul National University Hospital Institutional Review Board (IRB No. 2206-161-1335).